Self Concept and Social Anxiety Correlation in Adolescents: Korelasi Antara Konsep Diri dan Kecemasan Sosial pada Remaja - Aisyara Adianti Rahmah; Dwi Nastiti (Psikologia : Jurnal Psikologi, 2025)
This study examines the relationship between self-concept and social anxiety among senior high school students. General Background: Adolescent mental health remains a significant concern, particularly regarding emotional disorders in school settings. Specific Background: Social anxiety frequently emerges during adolescence and is associated with maladaptive self-perceptions. Knowledge Gap: Empirical evidence regarding the correlation between self-concept and social anxiety in the context of SMA Ma’arif Nu Pandaan remains limited. Aims: This study aims to determine the relationship between self-concept and social anxiety among students. Results: Using a quantitative correlational design with 167 students selected through simple random sampling, the findings revealed a significant negative correlation (r = -0.436, p < 0.001), indicating that higher self-concept scores are associated with lower social anxiety levels. Demographic analysis showed higher mean social anxiety scores among female students and those aged 17 years. Novelty: This research provides localized empirical data on adolescent psychological dynamics within an Indonesian senior high school context. Implications: The findings highlight the importance of strengthening positive self-concept development as part of school-based mental health strategies. Keywords: Self Concept, Social Anxiety, Adolescents, Correlational Study, School Psychology Key Findings Highlights Negative association identified between internal self-perception and anxiety symptoms Female students demonstrated higher mean anxiety scores Seventeen-year-old group showed the highest average anxiety level